Dream and sing. The knowledge of indigenous women in the Sierra Madre Occidental - Pacheco Ladrón de Guevara, Lourdes C. (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2018)
The present text puts into tension the status of universal validity of scientific knowledge before the contextualized knowledge of women in the Wixaritari indigenous communities of the Sierra Madre Occidental of Mexico. If science is based on a method that allows for the construction of certainties, demonstrable anywhere, the knowledge of indigenous women allows the survival of collectivities in specific places and times.